COMPARATIVE CHARACTERISTICS OF THE HEART MUSCLE STRUCTURE IN THE SIMULATION OF ATHEROSCLEROSIS IN RABBITS AND RATS - Hrynchak, N.M.; Piskun, R.P.; Shevchuk, T.I.; Vasenko, T.B. (World of Medicine and Biology, 2018)
This paper presents the results of biochemical, microscopic and micromorphometric studies of the hearts of rats and rabbits in normal state and in cholesterol atherosclerosis. The experimental atherosclerosis was simulated in white male rats weighing 150-200 g and male chinchilla rabbits weighing 3.0 – 4.7 kg. In rabbits, cholesterol was administered orally, added to grated carrots and sunflower oil, at a dose of 0.5 g/kg body weight for 3 months. In rats, cholesterol was administered by gavage with olive, pre-dissolved in sunflower oil, for 30 days daily, at a dose of 0.5 g/kg and, in the setting of thyroid depression with 4(6) - Methyl-2-thiouracil, at a dose of 12 mg/kg. In this simulation of the pathological condition, the signs of atherosclerotic changes of the heart structures in both types of laboratory animals have been observed. Histological examination of both rabbits and rats shows that many of the intramural arteries developed typical atherosclerotic plaques that result in drastic luminal occlusion, and sometimes there is diffuse lipid infiltration of all layers of the vessel walls and complete lumen obliteration. These changes in blood vessels cause ischemia and myocardial hypoxia.
Keywords: experimental atherosclerosis; blood lipids; myocardium; coronary arteries